The role of political decision-making processes and international cooperation in promoting peace and resolving armed conflict in Colombia - Martinez, Margarita Maria Bautista (2020)
This thesis analyses the Colombian government\'s decision-making process that involved international actors during the Havana peace process (2012-2016). The research highlights the influence of international actors in the government\'s decisions that worked to end the armed conflict between the government and the FARC-EP in Colombia. In particular, this study raises the following research question: How, and in what way, was the Colombian government\'s decision-making process influenced by international actors, especially the presence and actions of the UN, during the Havana peace process? The hypothesis of this research expects that the decision-making of the Colombian government during the Havana peace process had a key political condition of clearly defined involvement from international actors. It focuses on the Colombian Executive branch as the main actor and its relations with other national and international actors. To do so, the research references the theories of Foreign Policy Analysis, including the Governmental Politics Model and the Two-Level Game Model. This thesis provides an in-depth analysis of the Colombian government\'s decision-making process that involved UN cooperation by applying an interpretative case study. The research methodology is built on data collection gathered by interviewing a number of high-profile individuals involved in the Havana peace process including members of the Colombian government, members of the former guerrilla FARC-EP, United Nations Officials, and national and international academics and advisors who were involved in the decision-making during the negotiations. The conclusion goes on to argue that the Colombian decision-making process implemented during the negotiations was designed precisely to effectively define the role of international support, which improved the likelihood of success of the final peace agreement. The cooperation of international actors, especially from the UN, built trust between the negotiating parties regarding the sustainability of the negotiations. In addition, the international cooperation promoted institutional and political conditions that were necessary to achieve the final peace agreement.